SISTEM PENDAPATAN BAGI HASIL DAN PERLAKUAN AKUNTANSINYA PADA BANK SYARIAH MANDIRI (BSM) CABANG PADANG - Nurapia, Siti; Susanti, S.Pd, M.Si, Nora; Dahen, Lovelly Dwinda (Pendidikan Ekonomi, 2014)
ABSTRACTThis research aim to to know treatment of accountancy earnings of sharing holder BSM branch field and also compare according to treatment of Moslem law accountancy earnings of sharing holder BSM with rule of PSAK 105 that is about defrayal of and mudharabah of PSAK 106 that is about defrayal musyarakah. This Research typ deskriptf, where this descriptive research to know self-supporting variable score, goodness one variable or more ( independen) without making comparison, or attribute to other variable. While data collecting method taken by interview on the side of BSM, observation that is direct perception to BSM, and also documentation by collecting, copying, and evaluating reports and also documents exist in BSM. Pursuant to result of from interview wrongly one of BSM where activity of this BSM one of them which activity the core important association of fund of society. Where earnings of accepted sharing holder normal transaction / especial transaction [company that is obtained from defrayal of muadharabah and musyarakah. Earnings the accepted in the form of a number of cash as according to proportion which have been agreed on by both parties. From result of research expected will give clarification to society about how system earnings of sharing holder BSM defrayal of mudharabah and musyarakah and also its with PSAK 105 and PSAK 106